Validity and test-retest reliability of a patient-reported outcome measure for an outpatient cardiac rehabilitation programme. (2nd August 2019) - Cowie, Aynsley; Hair, Mario; Kerr, Emma; McKay, Janet; Allan, Lesley; Thomson, Patricia
Abstract : Background/Aims: This article details how a patient-reported outcome measure (PROM), termed PROM-CR1, was tested for acceptability, validity and test-retest reliability at the end of an outpatient cardiac rehabilitation programme. Methods: PROM-CR1 was completed by 138 service users (mean age 66.95 years, range 42–94 years; 115 males, 23 females; with a range of cardiac diagnoses), who used the tool at home twice: once at the end of the outpatient cardiac rehabilitation programme and 1 week later. Results: PROM-CR1 demonstrated good acceptability, construct and concurrent validity, and test-retest reliability. The construct validity analysis highlighted that one item required removal from the PROM-CR1. Conclusions: A finalised 30-item version of the tool will now be widely disseminated and further evaluated within cardiac rehabilitation clinical practice.